Konflik Pekerjaanâ€Keluarga dengan Kepuasan Kerja: Metaanalisis - Soeharto, Triana N. E. D. (Jurnal Psikologi, 2009)
This review examined the relationship between workâ€family conflict and job satisfaction. The quantitative review involved 7 studies from 11 articles.The metaanalysis results showed that workâ€family conflict has a correlation on job satisfaction. Result indicated that workâ€family conflict influence people`s feelings and attitudes about jobs. Future research should strive for examination of how sample influences findings.